Efficient Fractionation of Lignin- and Ash-Rich Agricultural Residues Following Treatment With a Low-Cost Protic Ionic Liquid - Chambon, Clementine L.; Chen, Meng; Fennell, Paul S.; Hallett, Jason P. (Frontiers in Chemistry, 2019)
Agricultural residues from rice, wheat and sugarcane production are annually available at the gigaton-scale worldwide, particularly in Asia. Rice and wheat residues are currently referred to as waste materials and often are disposed of by open-field burning or landfilling, resulting in a large amount of greenhouse gas emissions and air pollution. Due to their abundance, high carbohydrate and ash content, these agroresidues are most suitable for conversion to bioethanol, with potential to multiply current production by a factor of 14. However, these feedstocks are not presently used in commercial biofuels production processes due to low digestibility, linked to their high lignin content. In this work we demonstrate application of the low-cost protic ionic liquid triethylammonium hydrogen sulfate ([TEA][HSO4]) for pretreatment of rice straw, rice husk, wheat straw and sugarcane bagasse. The feedstocks had high ash (up to 13 wt%) and lignin content (up to 28 wt%). Pretreatment effectiveness was examined at 150 and 170 °C and was characterized by glucose release following enzymatic saccharification (i.e. hydrolysis), biomass delignification observed by compositional analysis, and lignin recovery. The isolated lignin fractions were analyzed by 2D HSQC NMR to obtain insights into the structural changes occurring during ionic liquid pretreatment. After treatment at 170 °C for 30–45 min, enzymatic hydrolysis of three agroresidues gave glucose yields approaching 90% while rice husk gave 73% yield. Glucose release from the pulps was enhanced by saccharifying wet pulps without an air-drying step to reduce hornification. According to pulp compositional analysis, up to 82% of lignin was removed from biomass during pretreatment, producing highly digestible cellulose-rich pulps. HSQC NMR of the extracted lignins showed that delignification proceeded via extensive cleavage of β-O-4’ aryl ether linkages which was accompanied by condensation reactions in the isolated lignins. The high saccharification yields obtained indicate excellent potential for valorization of low-cost agroresidues in large volumes, which is promising for commercialization of biofuels production using the ionoSolv pretreatment technology.